Keterlibatan Pengasuhan Orang tua Laki-Laki dan Efikasi Menjadi Ayah yang Empatik - Afifa Rifda Nabila; Budi Andayani (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
The aim of this study was to examine the relationship between a father’s involvement and his efficacy to an empathic father. Efficacy to an empathic father was measured using fathering efficacy scale developed by the researcher. Father’s involvement was measured using the Inventory of Father Involvement which modified by a researcher with alpha coefficient 0.992. The subject of this study were 80 fathers of the first children at the elementary age. The data were analyzed using product-moment correlation. The analysis showed a correlation coefficient of 0.442 (p<0.01). That means there was a significant relationship between efficacy on an empathic father and his father’s involvement. Father’s involvement explained 19.5 % of the variance in efficacy on an empathic father. The study showed that father involvement increased efficacy to be an empathic father.